1995
DOI: 10.1007/bf00186783
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in the rat cochlea: immunohistochemical and ultrastructural analysis

Abstract: Gap junctions in the rat cochlea were investigated using immunostaining for connexin26 and transmission electron microscopy. Electron microscopy of normal and pre-embedded immunostained material showed that there were gap junctions between and among all cells that light microscopy showed to have immunostained appositions. Light microscopy showed immunostaining between and among cell types that electron microscopy showed to be joined by gap junctions. Immunostaining for connexin26 was therefore taken as providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
465
1
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(491 citation statements)
references
References 49 publications
9
465
1
7
Order By: Relevance
“…Sparse staining for connexin 26 for cells in this region was also noted in the initial report on its localization in rat (Kikuchi et al 1995). The sparse staining for gap junction proteins in type IV and III fibrocytes could hardly be otherwise because electron microscopy observations show that these cell types seldom contact one another or other cell types (personal unpublished observations).…”
Section: Cytochemistry Of Type IV Fibrocytesmentioning
confidence: 54%
See 1 more Smart Citation
“…Sparse staining for connexin 26 for cells in this region was also noted in the initial report on its localization in rat (Kikuchi et al 1995). The sparse staining for gap junction proteins in type IV and III fibrocytes could hardly be otherwise because electron microscopy observations show that these cell types seldom contact one another or other cell types (personal unpublished observations).…”
Section: Cytochemistry Of Type IV Fibrocytesmentioning
confidence: 54%
“…Among fibrocyte types, variable staining for transport-related enzymes left ambiguities regarding the identity and properties of type IV fibrocytes (Spicer and Schulte 1991). The report that all fibrocytes within the spiral ligament of rats are connected by gap junctions (Kikuchi et al 1995), together with a variety of evidence from numerous laboratories, led to the realization that fibrocytes play key roles in K + ion uptake from perilymph and recycling of those ions back to endolymph. The reported gap junctional connectivity of all fibrocytes, together with imprecise information regarding cytochemical specializations of various cell types, has led to a common assumption that all fibrocytes within the ligament participate in K + ion recycling (e.g., Wang et al 2002;Qu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several possible routes for K + recycling have been proposed, including a lateral recycling pathway, whereby K + is reabsorbed through a K/Cl co-transporter in the supporting cells (Tectal and Dieter's cells) of the organ of Corti. K + may then move down its electrochemical gradient, passing between cells through gap junctions until reaching Type I spiral ligament fibrocytes (SLFs) and back to the stria vascularis [13], and also recycling routes through the perilymph to the spiral ligament, either above or below the endolymph compartment, and hence to the stria [14]. Another route is a medial recycling pathway through which excess K + is returned to the scala media through medial supporting cells, spiral limbus fibrocytes and interdental cells, all coupled by gap junctions, with transport into endolymph by Na-K-ATPase pumps present in the interdental cells [13][14][15].…”
Section: Auditory Structure and Functionmentioning
confidence: 99%
“…Experimental evidence from in vivo studies has suggested that K + in endolymph is sourced from perilymph, rather than from the blood supply (Wada et al 1979). This observation led to a hypothesis of a recirculation of K + through the cochlear tissues (Hibino and Kurachi 2006;Kikuchi et al 2000;Kikuchi et al 1995;Wangemann 2006;, which is summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%